Space filling of permethylated β‐cyclodextrin by volatile hydrophobic and hydrophilic guests in polyethylene glycol. Issue 2 (5th December 2018) - Onuchak, Lyudmila A.; Kuraeva, Yuliya G.; Evdokimova, Maria A.; Golov, Andrey A.
Abstract : The inclusion of volatile organic compounds of various classes in the permethylated β ‐cyclodextrin in an oligomeric solution of polyethylene glycol was investigated by inverse gas–liquid chromatography methods and by a stereochemical approach. It was established that the "guest–host" complexation process is influenced by the geometrical structure of the guest molecules, their chirality, and entropy factors. Abstract : The inclusion of volatile organic compounds of various classes in the permethylated β‐cyclodextrin in an oligomeric solution of polyethylene glycol was investigated by inverse gas–liquid chromatography methods and by a stereochemical approach. It was established that the "guest–host" complexation process is influenced by the geometrical structure of the guest molecules, their chirality, and entropy factors.